An empirical study on the intervention of self-compiled situational BaDuanJin on autistic adolescents (The Journal of the International Society of Chinese Health Practices, 2021)
Objective: Autism is one of the most representative diseases in a wide range of developmental disorders, which often occurs before the age of 3. The core obstacles are language and social communication disorders, abnormal emotional behaviors, and mental retardation, which seriously endanger their children's body and mental health growth. The incidence of autism has exploded in recent years. Because children need support and care throughout their lives, their patients are under tremendous pressure on the economic, spiritual, and social levels, and urgently need the attention and support of the whole society. However, there is currently no specific medicine for the treatment of autism, and most of them are based on one-to-one rehabilitation training. Existing intervention methods require high professional knowledge and technology of practitioners, and long-term rehabilitation training requires high time and economic costs, thus there is a need for more convenient and effective alternative rehabilitation methods for autism. BaDuanJin is one of Chinese traditional fitness guiding exercises, which is cooperated with mindfulness and breathing, as well as paying attention appearance and movements, to the to achieve the effect of fitness and healing. Numerous studies have shown that long-term exercise can strengthen the body, improve mood, regulate mental mood, and help alleviate many diseases. However, the application of BaDuanJin to adolescents with autism for rehabilitation intervention has not been reported yet. This research aims to explore the effect of the "Situational BaDuanJin" on autistic adolescents based on author’s long-term front-line work experience, and to provide reference and guidance for developing new rehabilitation methods and enriching physical education for children with special needs. Methods: Six teenagers with autism were selected as the research subjects. Among them, three boys and three girls were sixth graders, with an average age of 12.8 years, who were all diagnosed by the psychiatric specialist of a professional medical institution during their age of 2-4. Based on the traditional BaDuanJin exercise method, the study created the "Situational BaDuanJin" combined with the movement and behavior characteristics of children with autism, physical education needs and many years of personal first-line teaching experience. Six participants were instructed to the 4-month exercise, which ask subjects to exercise 3 times a week and 70 minutes each time (divided into 2 units, 10 minutes in between). Before and after the intervention, the "Autistic Child Development Assessment Form" was used to evaluate the participants' motor abilities (including gross and fine motor abilities), emotional behavior ability and social communication ability. This study aims to explore the effect of self-compiled "Situational BaDuanJin" on the rehabilitation of autism, and analyze and discuss the implementation of teaching guidance and the improvement of exercise programs by comparing the situational BaDuanJin before and after the exercise in the above three dimensions. Results: The initial evaluation of all 6 autistic teenagers showed that: *Xiao An: male, has tried various rehabilitation treatments in professional institutions before, but with little effect. The assessment showed that his language ability was severely degraded and he has no willingness to communicate with others, but has aggressive and self-harming behaviors. He has a lower cognition level than peers and loves to play in water. Due to the abnormal perception, he would constantly shake his fingers, and had poor coordination ability His ability of twisting, tearing and pulling finger was weak. *Xiaobing: male, has never had rehabilitation treatment. Parents complained that because xiaobing would like run around every day, they dare not take him to the streets or go to parks or supermarkets. His language delay, and he like to be alone. He has had self-harm behavior and his cognitive level was low. He didn’t like to wear new clothes and keep rotating his body; His hand-eye coordination was poor, so the coloring was out of style. *Xiao Chen: male, has participated in sensory integration training. The evaluation showed that his behavior was stereotyped. He often talks to himself in advertising words. He can communicate simply. He has self-harm behavior and often loses his temper. He has lower cognition level than peers. He likes rotating electric fans and constantly shaking the body back and forth. He has obesity and poor hands and eyes coordination and is unable to complete tracing exercises. *Xiaoding: female, has had experienced in box court rehabilitation training. The evaluation found that she had self-injurious behavior, tantrums, run around and prominent behaviors during adolescence. She often hit her own head, swing her back and forth while sitting in a chair and walk with heels. She can't cross-hop feet back and forth and unscrew the lid of the water bottle independently. *Xiaoyi: female, has trained in rehabilitation institutions continuously. The assessment showed that she has poor emotional control, stereotyped behavior, and subtle changes in life can cause tantrums and crying. She was able to express physical needs, such as "go to toilet", "I want to drink water". She has poor exercise ability and often paints or writes out of style, and cannot tie shoelaces. *Xiaofang: female, before the age of 6, had gone to kindergarten for half a day and trained in rehabilitation institutions for half a day. After the age of 7, she has entered an ordinary school and then transfers to a special school. She has good cognition level and no language barriers. She has stable emotion and good flexibility, but poor core and finger strength. She was unable to unscrew the lid of the water bottle and open the food bag. 2. Reassessment after intervention: Four months later, the "Autistic Child Development Assessment Form" was used again to re-evaluate 20 items in the three dimensions of exercise ability, emotional behavior, and social interaction. Six participants have improved to varying degrees respectively. Among them, Xiaofang’s improvement was remarkable, with 18 items in total, while Xiaobing only improved with 11 items. Conclusion: "Situational BaDuanJin" helps to improve the athletic ability of autistic teenagers, improve their adolescent mood and behavior regulation ability, and promote the social communication ability; especially for those with better cognition and/or stereotyped behavior, emotional problems and poor hand-eye coordination, the rehabilitation effect of autistic adolescents is more obvious. In the future, it is expected to further improve the "Situational Baduanjin" teaching program for autistic teenagers with different symptoms and functional levels, and to attract parents and other teachers to actively participate, guide and accompany autistic teenagers in long-term exercise to improve the effect of exercise.